(untitled) (Journal of Asian Development Studies, 2023)
Mountain agriculture is the linchpin of the economy in Pakistan’s Hindu Kush Karakoram and Himalaya mountain regions. Currently, mountain agriculture is in a state of transition, experiencing rapid changes and innovation due to physical and anthropogenic drivers, resulting in far-reaching consequences on the livelihood sustainability and food security of the local people. This study explores the multifaceted drivers of agricultural transformation in the Eastern Hindu Kush region, specifically in Lotkuh Valley, Pakistan, focusing on the intricate relationship between resilience-building measures and the adoption of innovative agricultural practices. For this purpose, data were explored from both primary and secondary sources. Primary data were collected using stratified sampling techniques during extensive field surveys conducted in the study area from 2017 to 2019. Remotely sensed data from 1990 to 2019 were obtained from the USGS site. Secondary data were acquired from the Gazetteer of Chitral 1928, Census Report 1961-2017, and Rural Settlement Report 1988. The collected data have been analyzed through descriptive analysis and advanced geospatial techniques. The findings reveal that vivid changes and transformations have occurred in mountain agriculture. These transformations include land use/cover changes, agricultural land holdings, cropping patterns, livestock populations, arboriculture, etc. From the findings of this study, it is inferred that innovation in mountain agriculture entails a variety of opportunities and has increased agricultural production, resulting in a positive impact on the economy, food security, and livelihood sustainability. This study provides nuanced knowledge and insights for policymakers, mountain agriculturists, and practitioners to effectively develop sophisticated strategies for achieving the ambitious goal of zero hunger and poverty eradication.